The cost of consumption: an analysis of the heterogeneous impacts of groundwater availability in the High Plains aquifer - Moore, Lacey, author; Suter, Jordan, advisor; Goemans, Chris, committee member; Schipanski, Meagan, committee member (Colorado State University. Libraries, 2019)
Nearly 20-percent of the wheat, corn, cotton and cattle produced in the United States are made possible by the hydrologic resources of the High Plains Aquifer (HPA) (NRCS, 2017). Despite being a source of agricultural prosperity, this aquifer has long been subject to overdraft including reductions in saturated thickness exceeding 50m in the southern extents (Haacker et al., 2016). We follow Hornbeck et al. (2014, 2015) in comparing economic outcomes among counties inside the HPA to similar counties within 100km from the aquifer boundary, building on this research by also evaluating the impact of initial groundwater endowments as an exogenous measure of irrigation access. Utilizing a hedonic pricing model based on Ricardian theory of land valuation, we choose to examine irrigation intensity, land values, and population density using census data at the county scale to measure the marginal benefit of groundwater. These economic outcomes are examined across ranked groupings of initial saturated thickness for three distinct time periods: approximate pre-development of the aquifer (1925-1945), during the height of irrigation expansion (1950-1992), and during contemporary time periods of irrigation water shortages (1997-2012). Results indicate that previous studies which have regarded the HPA as a homogeneous unit overlook the true marginal contributions of groundwater. We find that the counties with the largest initial endowments of groundwater in the HPA have increased land values by as much as 42-percent during the height of irrigation expansion, and more importantly have maintained the longest lasting economic benefits compared to counties with lower initial saturated thickness and those outside the aquifer. Our results differ from previous studies (i.e., Feng et al., 2012) as we find no statistical relationship between access to groundwater (or aquifer depletion) and population density.
Keywords: economics; hedonic; Ricardian; groundwater; aquifer; Ogallala